Special Report– A Guide to Implementation of Statement 106 on Employer's Accounting for Postretirement Benefits Other Than Pensions– Questions and Answers. - Mittelstaedt, H. Fred; Boatsman, James R. (The Accounting Review, 1994)
Abstract Reviews the book `Special Report–A Report Guide to Implementation of Statement 106 on Employers' Accounting for Postretirement Benefits Other Than Pensions–Questions and Answers,' by K.E. Dakdduk and Jules M. Cassel.